2002
DOI: 10.1007/s701-002-8270-1
|View full text |Cite
|
Sign up to set email alerts
|

The One-Piece Orbitozygomatic Approach: The MacCarty Burr Hole and the Inferior Orbital Fissure as Keys to Technique and Application

Abstract: Understanding the MacCarty keyhole burr hole and the microsurgical anatomy of the inferior orbital fissure is essential to performing the FTOZ1 approach. The three types of FTOZ1 approach enable the surgeon to tailor the approach according to the surgical exposure needed for each lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…During the orbitozygomatic osteotomy, the most inferior zone point was determined as the ZFF (Aziz et al, 2002;Gonzalez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the orbitozygomatic osteotomy, the most inferior zone point was determined as the ZFF (Aziz et al, 2002;Gonzalez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that the ZFF may be a useful anatomical landmark for the depth of facial dissection near the bone (Aziz et al, 2002;Gonzalez et al, 2002;Martins et al, 2003). The zygomatic nerve and its branches may be injured during facial surgery in the periorbital region (Mangal et al, 2004;Lei et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the one-piece technique, it is paramount to create a generous MacCarty bur hole that exposes 3 components: 1) frontal lobe dura, 2) orbital roof, and 3) periorbita). 3 The orbital rim is disarticulated with the frontotemporal bone flap as one piece using an osteotome and fracture technique. An orbital osteotomy is made just lateral to the supraorbital notch, inferior to the frontozygomatic suture, and across the orbital roof through the MacCarty bur hole.…”
Section: Modified One-piece Orbitozygomatic Approach: Technical Pearlmentioning
confidence: 99%
“…The 1-piece variant of the orbitozygomatic approach has been extensively studied. [2][3][4]10,17,19,21 One anatomical study on this approach found a decrease in the amount of orbital roof removed in the 1-piece variant, which limited the exposure to structures, working angles, and illumination. 21 Nevertheless, the 1-piece orbitozygomatic approach is routinely used at many centers.…”
Section: Discussionmentioning
confidence: 99%